Comparative Effectiveness of Operative Versus Nonoperative Treatment for Rotator Cuff Tears: A Propensity Score Analysis From the ROW Cohort. Issue 13 (November 2019) - Jain, Nitin B.; Ayers, Gregory D.; Fan, Run; Kuhn, John E.; Warner, Jon J.P.; Baumgarten, Keith M.; Matzkin, Elizabeth; Higgins, Laurence D.
Background: The evidence to support operative versus nonoperative treatment for rotator cuff tears is sparse and inconclusive. Purpose: To assess pain and functional outcomes in patients undergoing operative and nonoperative treatments for rotator cuff tears. Study Design: Cohort study; Level of evidence, 3. Methods: From March 2011 to February 2015, a multicenter cohort of patients with rotator cuff tears undergoing operative and nonoperative treatments was recruited. Patients completed a detailed history questionnaire, the Shoulder Pain and Disability Index (SPADI), and the American Shoulder and Elbow Surgeons (ASES) standardized form and underwent magnetic resonance imaging. In addition to baseline assessments, patients received follow-up questionnaires at 3, 6, 12, and 18 months. Propensity score weighting was used to balance differences in characteristics of the operative and nonoperative groups. Results: Adjusted for propensity scores, the operative (n = 50) and nonoperative (n = 77) groups had similar characteristics, as evidenced by the small standardized mean differences between the groups. Adjusted mean differences in the SPADI and ASES scores between the operative and nonoperative groups were –22.0 points (95% CI, –32.1 to –11.8) and –22.2 points (95% CI, –32.8 to –11.6) at 18 months, respectively. The operative group had a significantly higher proportion of patients who showed ≥30% ( P = .002) and ≥50% ( P < .0001) improvement in SPADI and ASES scores as compared with the nonoperative group. Conclusion: In this prospective cohort study, patients undergoing operative treatment had significantly better pain and functional outcomes as compared with patients undergoing nonoperative treatment for rotator cuff tears. Differences between the 2 groups in SPADI and ASES scores at the 6- to 18-month time points met the minimal clinically important difference (depending on the threshold used). A large randomized controlled trial is needed to answer this question more definitively.